Primer on artificial intelligence and robotics - Manav Raj; Robert Seamans (Journal of Organization Design, 2019)
This article provides an introduction to artificial intelligence, robotics, and research streams that examine the economic and organizational consequences of these and related technologies. We describe the nascent research on artificial intelligence and robotics in the economics and management literature and summarize the dominant approaches taken by scholars in this area. We discuss the implications of artificial intelligence, robotics, and automation for organizational design and firm strategy, argue for greater engagement with these topics by organizational and strategy researchers, and outline directions for future research.
Keywords: 650; Automation; Artificial intelligence; Robotics; Future of work; Organizational design